Hábitos alimentarios del Pecarí de collar (Pecari tajacu) en un bosque tropical caducifolio de Jalisco, México - Martínez Romero, Luis Enrique; Mandujano, Salvador (Instituto de Ecología, A.C., 1995)
The principal components of the diet of the collared peccary (Pecari tajacu) and its variation along the time, were deterrnined in a tropical dry forest of the Biological Station of "Chamela" in Pacific Coast of Jalisco State in México, between May 1992 and May 1993. The method used was the feces analysis: four componentes were identified in the feces: leaves-branches, roots, fruits and undefined. A total of 162 feces were analyzed. The two principal componentes in the annual diet were roots (47,9%) and leaves-branches (41.2%). Fruits contributed with the 10,6% of annual diet and the undefined cornponenet less than 1 %. The principal fruits were: Opuntia excelsa, Ficus spp., Brosimum alicastrum, Sideroxylon capiri, Spondias purpurea, Vitex mollis and unidentified leguminóse. Arthropods were not found in the feces. The percentage of each component in the diet and its variation along the time, were relatod with the availability of the plant resource in this tropical forest. High consume of loaves-brnnches were in wet season and high consume of roots in dry season. The results of the peccary diet in the study site is in agreement with the found in others tropical dry forests except for the fruits that were in less percentage. It's recommendable study the role of the collared peccary as depredator and disperse agent of some seed-plant species in this tropical dry forest.